Profile of Obstetrics Fistula Clients; is the trend changing? - Morhason-Bello, IO; Bello, OO; Abduls-Salam, RA; Babawarun, TO; Lawal, OO; Ojengbede, AO (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To assess the changes in the profiles of obstetric fistula clients. Methods: This was a retrospective review of the medical records of all obstetric fistula clients managed by the Oyo state fistula team at University College Hospital and Adeoyo Maternity Hospital Ibadan, Nigeria. A proforma was used to extract information on socio-demographic and obstetric characteristics of clients and was analyzed using SPSS 25.0. Level of significance was set at P <0.05. Results: The median age and number of pregnancy with occurrence of fistula were 34 years and 2 respectively. Above a quarter (32.2%) had at least secondary level of education, three quarter (75.2%) were currently married and about half were traders. Only 20 (22%) booked the pregnancy that resulted in fistula with 44 (44.9%) delivering through cesarean section. Majority 70 (72.9%) of the fetuses were stillbirth. Conclusions: The widely held believe of a typical obstetric patient still holds but substantial cases of fistula occurred in multiparous women and at older age.